PEMANFAATAN IKAN BANDENG (Chanos chanos) MENJADI PRODUK BERNILAI EKONOMIS TINGGI DI DESA BONTO BAHARI KEC. BONTOA KAB. MAROS - Kasmawati, Kasmawati; Hasrun, Hasrun; Ernaningsih, Ernaningsih; Hamsiah, Hamsiah (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2022)
Bonto Bahari Village, Maros Sul-Sel Regency is one of the milkfish producing areas The main problem faced by this village is that when harvest time comes, milkfish commodities are abundant so that their selling value decreases and even causes losses to pond farmers. Laskar Jaya Bahari farmer group together with the community partnership program team from the Indonesian Muslim University (UMI) are looking for solutions to the problems mentioned above, so the efforts made are the Utilization of Milkfish (Chanos Chanos) into High Economic Value Products. Community service activities were carried out on September 28, 2020 in sabanga hamlet, Bonto Bahari Village, Bontoa Regency, Maros Regency with group partner "Laskar Jaya Bahari.. Such efforts are expected to increase the income of partners, create new jobs which in turn improves the welfare of the community . The expected output target is an increase in the understanding, knowledge and skills of the farmer group "YH Laskar Jaya Bahari about 1. Techniques for pulling out thorns and packaging whitefish 2. Frying technique of whitefish crispy and 3. Knowing how to manage PIRT and Halal certification from MUI. Based on the results of the implementation of the community partnership program for members of the YH Laskar Jaya Bahari group, it is optimistic that it will increase income by increasing the selling value of milkfish by preparing milkfish products without thorns and crispy milkfish with packaging that already has PIRT and halal certification.